Associations between the gut microbiota and host immune markers in pediatric multiple sclerosis and controls. Issue 1 (December 2016) - Tremlett, Helen; Fadrosh, Douglas; Faruqi, Ali; Hart, Janace; Roalstad, Shelly; Graves, Jennifer; Spencer, Collin; Lynch, Susan; Zamvil, Scott; Waubant, Emmanuelle
Abstract Background As little is known of association(s) between gut microbiota profiles and host immunological markers, we explored these in children with and without multiple sclerosis (MS). Methods Children ≤18 years provided stool and blood. MS cases were within 2-years of onset. Fecal 16S rRNA gene profiles were generated on an Illumina Miseq platform. Peripheral blood mononuclear cells were isolated, and Treg (CD4+ CD25hi CD127low FoxP3+ ) frequency and CD4+ T-cell intracellular cytokine production evaluated by flow cytometry. Associations between microbiota diversity, phylum-level abundances and immune markers were explored using Pearson's correlation and adjusted linear regression. Results Twenty-four children (15 relapsing-remitting, nine controls), averaging 12.6 years were included. Seven were on a disease-modifying drug (DMD) at sample collection. Although immune markers (e.g. Th2, Th17, Tregs) did not differ between cases and controls (p  > 0.05), divergent gut microbiota associations occurred; richness correlated positively with Th17 for cases (r  = +0.665, p  = 0.018), not controls (r  = −0.644, p  = 0.061).Bacteroidetes inversely associated with Th17 for cases (r  = −0.719, p  = 0.008), not controls (r  = +0.320, p  = 0.401).Fusobacteria correlated with Tregs for controls (r  = +0.829, p  = 0.006), not cases (r  = −0.069, p  = 0.808). Conclusions Our observations motivate further exploration to understand disruption of the microbiota-immune balance so early in the MS course.